Cation self-diffusion of 44Ca, 88Y, and 96Zr in single-crystalline calcia- and yttria-doped zirconia - Kilo, M. (2003)
Self-diffusion of calcium, yttrium, and zirconium in single-crystalline YSZ and CSZ (YSZ: yttria-stabilized zirconia; containing 10 to 32 mol % Y2O3 ; CSZ: calcia-stabilized zirconia; containing 11 and 17 mol % CaO) was measured at temperatures between 960 and 1700 °C. For zirconium and calcium diffusion, the stable isotopes 44Ca and 96Zr were used as tracers and the samples were analyzed with secondary ion mass spectrometry. In the case of yttrium diffusion, the radioactive tracer 88Y was used and an abrasive sectioning technique was applied. Zirconium bulk diffusion is slower than yttrium and calcium bulk diffusion, and there is a nearly linear correlation of diffusion coefficient with cation radius. In YSZ, zirconium and yttrium bulk diffusivity are maximum for a stabilizer content of 10–11 mol %, while in CSZ both calcium and zirconium tracer diffusion are independent of the calcium content. The activation enthalpy of yttrium stabilizer bulk diffusion (4.2 eV) is, as in CSZ, slightly smaller than for zirconium bulk diffusion (4.5 eV). The yttrium dislocation pipe diffusivity is five to six orders of magnitude faster than the bulk diffusivity, and its activation enthalpy (3.5 eV) is also smaller than that of the bulk diffusion. From the activation enthalpy and from the concentration dependence of the cation bulk diffusion, it is concluded that the cation diffusion occurs either via free vacancies (V48 Zr in YSZ) or via bound vacancies ([V48 Zr-2V2•O]x in CSZ)